경북 북부지역 생활폐기물 성상분석을 통한 온실가스 배출량 추정 기초연구 - 이동섭(Dong Sub Lee); 박강우(Gang Woo Park); 심영석(Sim Young Seok) (Daehan hwan'gyeong gonghag hoeji, 2024)
정부 및 지자체는 국가 온실가스 감축목표(NDC: Nationally Determined Contribution) 달성을 위해서 폐기물부문에서의 폐기물의 감량 및 재활용률을 대폭 확대하고 있는 실정이다. 경북 북부지역 생활폐기물은 광역 쓰레기처리시설인 ‘맑은누리파크’에서 11개 북부지역 자치단체의 생활폐기물을 소각하고 있으며 소각 및 자원회수시설에서발생하는 온실가스 저감을 위하여 생활폐기물의 면밀한 성상분석 및 실태조사가 필요한 실정이다. 성상분석은 3계절(봄, 여름, 가을)에 걸쳐 전체 1,110.4 kg의 생활폐기물을 분리 조사하였고, 종이류가 259.5 kg(23.4%)로 가장 많았으며,차순위로 기타 256.8 kg(23.1%) > 비닐류 241.6 kg(21.8%) > 플라스틱류 99 kg(8.9%) 등의 순으로 분석되었다. 경북북부권 생활쓰레기의 성상비율에 있어, 재활용폐기물이 695.2 kg(63.0%)로 가장 많은 비중을 차지하는 것으로 조사되었으며, 차순위로 소각용 321.5 kg(29.2%), 음식물류 82.5 kg(7.4%), 유해폐기물 2.4 kg(0.2%), 매립용 1.8 kg(0.2%)로 조사되어 반입되는 생활폐기물의 분리배출에 대한 홍보가 시급한 것으로 분석되었다. 2022년 반입된 경북북부권 생활쓰레기 소각으로 인한 온실가스 발생량 추정결과 총 온실가스 배출량은 75,052.4tCO2eq 이며 안동시가 28,217.6tCO2eq으로가장 많은 것으로 조사되었고, 차순위로 영주시 13,462.3tCO2eq, 상주시 7,426.1tCO2eq 순으로 높은 것으로 분석되었다. 2022년 맑은누리파크 반입량 기준 시･군별 감축량은 온실가스 총 감축량은 12,012.94tCO2eq이며, 이 중 안동시가4,637.52tCO2eq 감축으로 감축량이 가장 많고, 차순위로 영주시 1,938.18tCO2eq, 상주시 1,133.48tCO2eq 순으로 분석되었다. 성상별 감축량의 경우 플라스틱류가 11,779.7tCO2eq로 가장 많이 감축되는 것으로 나타났으며, 차순위로 고무피혁류 152tCO2eq, 종이류 59.1tCO2eq, 기타 생활 폐기물류 18.6tCO2eq로 추정되었다. 본 연구는 소각 및 자원회수시설에반입되는 시, 군별 생활폐기물 성상분석을 통하여 온실가스 발생이 높은 성상(플라스틱류, 고무피혁류) 등의 비율확인하였고 향후 지자체 생활폐기믈 재활용 정책의 기초자료로 활용할 수 있다. In order to achieve the National Greenhouse Gas Reduction Target, the government and Gyeongsangbuk-dowaste sector are planning to significantly expand the waste reduction and recycling rate. Household waste in thenorthern part of Gyeongsangbuk-do burns household waste from 11 northern local governments at “Clear Nuri Park”,a wide-area waste treatment facility, and close properties and surveys of household waste are needed to reducegreenhouse gases generated by incineration and resource recovery facilities. Constellation analysis investigated atotal of 1,110.4 kg of household waste over three seasons (spring, summer, and fall), with paper being the mostcommon with 259.5 kg (23.4%), followed by other 256.8 kg (23.1%) > vinyl 241.6 kg (21.8%) > plastic 99 kg(8.9%). Recycling waste accounted for the largest proportion of household waste in the northern part of NorthGyeongsang Province with 695.2 kg (63.0%), followed by incineration with 321.5 kg (29.2%), food logistics with82.5 kg (7.4%), hazardous waste with 2.4 kg (0.2%), and landfill with 1.8kg (0.2%). According to the estimationof greenhouse gas generation from the incineration of household waste in the northern part of Gyeongsangbuk-doin 2022, the total greenhouse gas emission was 75,052.4tCO2eq, and Andong City was the largest with28,217.6tCO2eq, followed by Yeongju City with 13,462.3tCO2eq and Sangju City with 7,426.1tCO2eq. Based on theamount brought into Clear Nuri Park in 2022, the total reduction of greenhouse gases was 12,012.94tCO2eq, ofwhich Andong City had the largest reduction with 4,637.52tCO2eq reduction, followed by Yeongju City with1,938.18tCO2eq and Sangju City with 1,133.48tCO2eq. In the case of reduction by constellation, plastics werefound to be the most reduced to 11,779.7tCO2eq, followed by rubber leather 152tCO2eq, paper 59.1tCO2eq, andother household wastes 18.6tCO2eq. It is necessary to check the ratio of properties with high greenhouse gases(plastics and rubber leather) through the analysis of household waste properties by city and county. KCI Citation Count: 0